TOWARDS CAMPUS SUSTAINABILITY : ESTIMATING ON-CAMPUS VEHICLE CO2 EMISSIONS IN UNIMAS - Mohamad Raduan, Kabit; Jeffery Lee Siong, TING; Abdullah, Yassin (Penerbit UMT, 2022)
Carbon dioxide (CO2 ) emission from motor vehicles is a one of major contributing factors to global warming. Efforts to reduce CO2 emissions should involve all parties including universities. In 2017, Universiti Malaysia Sarawak (UNIMAS) has committed to reduce CO2 emissions from its campus upon joining the low-carbon campus initiative. Thus, the current study aims to estimate the baseline of on-campus vehicle CO2 emissions by using mobility analysis of 5,294 entry vehicle data from two main gates (West and East) and 15 parking zones in the campus. Parking volume observations and traffic assignment analysis using the Bureau of Public Roads functions were undertaken to determine the links’ volumes. Subsequently, vehicle CO2 emissions were derived from the estimated vehicle fuel consumption. The results reveal that a total of 1,333.4 kg of CO2 emissions were expelled by on-campus motorised vehicle movements (which were predominantly petrol cars that comprised 80% of the observed vehicle trips). Additionally, the study discovered that the average on-campus vehicle CO2 emission was 12.4 kg per kilometre which far exceeds the European Standard for road traffic CO2 emissions. Thus, to achieve the status of a low-carbon campus, it is imperative for the university management to properly address Sector 3 CO2 emissions from the transportation segment by employing effective strategies and policies to significantly reduce private vehicle dependency among university staff and students.